New and emerging AAC technology supports for children with complex communication needs and their communication partners: State of the science and future research directions. (2nd January 2019) - Light, Janice; McNaughton, David; Caron, Jessica
Abstract: This paper discusses recent research and development with a specific focus on selected new and emerging research-based augmentative and alternative communication (AAC) technologies that are developmentally appropriate and responsive to the individual interests, needs, and skills of children with developmental disabilities, their families, peers, and other communication partners. Specifically, this paper reviews the state of the science and future directions related to recent research and development of AAC technologies as supports to (a) enhance language learning, (b) facilitate social interaction, (c) improve literacy skills, (d) increase participation in society, and (e) teach interaction strategies to communication partners.